Linking Silica Support Morphology to the Dynamics of Aminopolymers in Composites - Carrillo, Jan-Michael Y (Langmuir : the ACS journal of surfaces and colloids, 2017)
A combined computational and experimental approach is used to elucidate the effect of silica support morphology on polymer dynamics and CO2 adsorption capacities in aminopolymer/silica composites. Simulations are based on coarse-grained molecular dynamics simulations of aminopolymer composites where a branched aminopolymer, representing poly(ethylenimine) (PEI), is impregnated into different silica mesoporous supports. The morphology of the mesoporous supports varies from hexagonally packed cylindrical pores representing SBA-15, double gyroids representing KIT-6 and MCM-48, and cagelike structures representing SBA-16. In parallel, composites of PEI and the silica supports SBA-15, KIT-6, MCM-48, and SBA-16 are synthesized and characterized, including measuring their CO2 uptake. Simulations predict that a 3D pore morphology, such as those of KIT-6, MCM-48, and SBA-16, will have faster segmental mobility and have lower probability of primary amine and surface silanol associations, which should translate to higher CO2 uptake in comparison to a 2D pore morphology such as that of SBA-15. Indeed, it is found that KIT-6 has higher CO2 uptake than SBA-15 at equivalent PEI loading, even though both supports have similar surface area and pore volume. However, this is not the case for the MCM-48 support, which has smaller pores, and SBA-16, whose pore structure rapidly degrades after PEI impregnation